2016
DOI: 10.1111/andr.12220
|View full text |Cite
|
Sign up to set email alerts
|

The impact of premature ejaculation on the subjective perception of orgasmic intensity: validation and standardisation of the ‘Orgasmometer’

Abstract: SUMMARYTo the best of our knowledge, no psychometric tools have been specifically developed to measure if premature ejaculation (PE) is related to low sexual pleasure in terms of perception of orgasmic intensity. Hence, the aim of this study was to evaluate if men with PE suffer from a low perception of orgasmic intensity using a new tool, the 'Orgasmometer', to quantitatively measure the intensity of orgasmic pleasure. Among 329 subjects attending our andrological unit for suspected PE, 257 men fulfilled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…This index was defined as the number of individuals having a score beyond the limit of agreement (LOA), defined by the lines +1.96 sd and −1.96 sd . An index within the 5% suggests agreement between two methods . In our analysis, the number of individuals having a score beyond the LOA, defined by the lines ±1.96 sd , was equal to 6 providing a Bland–Altman index of 6%, confirming an agreement between the two methods.…”
Section: Resultssupporting
confidence: 74%
“…This index was defined as the number of individuals having a score beyond the limit of agreement (LOA), defined by the lines +1.96 sd and −1.96 sd . An index within the 5% suggests agreement between two methods . In our analysis, the number of individuals having a score beyond the LOA, defined by the lines ±1.96 sd , was equal to 6 providing a Bland–Altman index of 6%, confirming an agreement between the two methods.…”
Section: Resultssupporting
confidence: 74%
“…Premature ejaculation is a common male sexual dysfunction which is poorly understood and can lead to a low perception of orgasmic intensity and female sexual dysfunction (FSD) (Limoncin et al, ; Maseroli et al, ). Nowadays, a problem exists in assessing the prevalence of PE is the lack of a validated definition of the PE (Waldinger, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in previous studies that sexual dysfunction relates to a wide series of psychological problems, such as general anxiety and depression (Althof, ; Gao et al, , ; Hale & Strassberg, ; Rowland, ; Rowland & Cooper, ; Zhang et al, ). An observational study (Limoncin et al, ) (using the orgasmometer) conducted in Rome showed that men affected by premature ejaculation perceived significantly lower orgasmic intensity than sexually healthy men. Another study (Rowland, Patrick, & Gagnon, ) (with the usage of validated measurement) showed that PE patients reported lower levels of sex function and harder to be fulfilled by sex and higher incidences of psychological and psychiatric distress comparing with men without PE.…”
Section: Introductionmentioning
confidence: 99%
“…Being the ejaculatory mechanism itself unrelated to the lifestyle, the unique logical explanation of this effect could be the very frequent comorbidity between ejaculatory and ED [43][44][45], where one exacerbates the other. Moreover, physical exercises improve self-esteem and body image, which are negatively influenced in subjects with PE [46].…”
Section: Physical Activitymentioning
confidence: 99%